Decreasing Time to Pain Relief for Emergency Department Patients with Extremity Fractures. Issue 1 (28th December 2016) - Heilman, James A.; Tanski, Mary; Burns, Beech; Lin, Amber; Ma, John
Abstract : Significant delays occur in providing adequate pain relief for patients who present to the emergency department (ED) with extremity fractures. The median time to pain medication administration for patients presenting to our ED with extremity fractures was 72.5 minutes. We used a multidisciplinary approach to implement three improvement cycles with the goal of reducing the median time to pain medication by 15% over an eight month time period. First, we redesigned nursing triage and treatment processes. Second, we improved nursing documentation standardization to ensure accurate tracking of patients who declined pain medication. Third, through consensus building within our physician group, we implemented a department-wide standard of care to provide early pain relief for extremity fractures. Median time to pain medication for patients with an extremity fracture reduced significantly between the pre-and post-intervention periods (p=0.009). The average monthly median time to medication was 72.5 minutes (95% CI: 57.1 to 88.0) before the intervention (Jan 2013-Oct 2014) and 49.8 minutes (95% CI: 42.7 to 56.9) after the intervention (November 2014 to June 2016). In other words, monthly median time was 31% faster (22.7 minute difference) in the post intervention period. Implementing three key interventions reduced the time to pain medication for patients with extremity injuries. Since June 2016 the reductions in median time to medication have continued to improve.